An Integrated Approach to Manage The Rhizome Rot Disease of Ginger - Islam, MM; Khatun, F; Faruk, MI; Rahman, MM; Hossain, MA (Bangladesh Journal of Agricultural Research, 2022)
An experiment was conducted at Gazipur, Bogura and Ramgarh to observe the effect of eight different treatments packages on rhizome rot of ginger. The package comprising of seed treated with Chlorox (10%) + Soil treatment with Stable Bleaching Powder (20 kg/ha) + Soil drenching with Chlorox (10%) and Ridomil (0.2%) alternately for 5 times each gave superior or better results in respect of germination(80-97%), disease reduction(50-62%) and crop yield (24 t/ha) of ginger in all locations. The same package showed disease reduction ranging from 53 to 57.33% at Nilphamari, Rangpur, Bogura, Madhupur and Ramgarh in the validation trials and thereby produced higher yield of ginger 24.8 t/ha at Bogura, 23.6 t/ha at Rangpur, 23.2 t/ha at Nilphamari and 22.6 t/ha at Ramgarh. The same package also gave higher benefit cost ratio (BCR) of 4.85 in case of experiment and 4.58 in case of validation trials. This package was therefore seemed to be cost effective in reducing rhizome rot disease of ginger and accelerate the yield if applied properly. Bangladesh J. Agril. Res. 45(1): 1-9, March 2020